A new strategy for improvement of tamarind seed based chicken diet after microbial detannification and assessment of its safety aspects - Jana, Arijit; Adak, Atanu; Haider, Suman Kumar; Das, Arpan; Paul, Tanmay; Mondal, Keshab Chandra; Mohapatra, Pradeep Kumar Das (Acta Biologica Szegediensis, 2015)
Tamarind seed, an abundant agricultural waste, contains a large amount of naturally occurring anti-nutrient, tannin. This study aimed at evaluating the detannification efficiency of tannase producing Bacillus subtilis PAB2 in comparison with enzymatic and conventional physical techniques, and assessment of its health promoting effect in chicken model. Microbial fermentation resulted in lowering of 80.8% tannin, whereas enzymatic and physical treatment removed only 48 and 28.6%, respectively. To assess the health beneficial effects, experimental schedule for poultry chicken model was designed viz., (T1) commercial food, (T2) T1+tamarind seeds, (T3) T1+enzymatic detannified seeds and (T4) T1+ fermented seeds. It was found that physiological indices of chicken in T4 group improved more than T2, but those were comparable with T1 and T3. The level of total plasma protein, albumin and other haematological parameters also significantly (P<0.05) improved in T4 more than T2. The quantities of small intestinal indicator microbes like Escherichia coli, Clostridium perfringens and Yeast sp. in T4 group increased more than T2. Thus, fermentation led to quality improvement of raw tamarind seed which suggested its employment as an alternative feedstock for poultry chicken.